Tacloban City's center for urban farming and food security integrating urban aquaponics into sustainable housing developments for farmers and fisherfolks - Marquez, Marie Angelie U.
Tacloban City is a rapidly urbanizing city in the Region VIII. Despite being the region's capital, it has been lagging in terms of agricultural and fisheries production due to the reconversion of lands after Super Typhoon Yolanda. Looking into the future of the city, population growth is seen as inevitable. With the fast rate of urbanization and higher population growth rate, food insecurity is seen as inevitable. With more lands to be converted into urban dwellings, the city will lose its agricultural lands to the developers of the city. With these concepts in mind, comes the thesis problem of the problem is how can architecture solve and support the demands of the inevitable population growth and its complications. A market structure can be found within the CBD and with its current use. the conditions and activity of this facility